Quantification of Polyphosphate in Microalgae by Raman Microscopy and by a Reference Enzymatic Assay - Moudříková, Šárka; Sadowsky, Andres; Metzger, Sabine; Nedbal, Ladislav; Mettler-Altmann, Tabea; Mojzeš, Peter (Analytical chemistry, 2017)
Polyphosphates have occurred in living cells early in evolution and microalgae contain these important polymers in their cells. Progress in research of polyphosphate metabolism of these ecologically as well as biotechnologically important microorganisms is hampered by the lack of rapid quantification methods. Experiments with the green alga Chlorella vulgaris presented here compared polyphosphate extraction in water, methanol-chloroform, and phenol-chloroform followed by polyphosphate purification by binding to silica columns or ethanol precipitation. The phenol-chloroform extraction of C. vulgaris followed by ethanol precipitation of polyphosphate was shown to be superior to the other tested method variants. Recovery test of added polyphosphate standard to algal biomass showed that the method is accurate. Using this biochemical assay as a validated reference, we show that 2-dimensional, confocal Raman microscopy can serve as a linear proxy for polyphosphate in C. vulgaris with R2 up to 0.956. With this, polyphosphate quantification can be shortened by use of Raman microscopy from days to hours and, additionally, information about intracellular distribution of polyphosphate and heterogeneity among individual cells in algal culture can be obtained. This offers new insights into the dynamics and role of these polymers crucial for phosphorus uptake and storage. This analytical capability is of particular practical importance because algae aid phosphorus sequestration from wastewater and the thus enriched biomass may serve as organic fertilizer. Both these applications have a strong potential in a future sustainable, circular bioeconomy.
Keywords: hydrolasy působící na anhydridy kyselin; Acid Anhydride Hydrolases; Saccharomyces cerevisiae; Waste Water; Chlorella vulgaris; polyfosfáty; Wastewater; Polyphosphates; Spectrum Analysis, Raman; Ramanova spektroskopie; odpadní voda